Interconnection Study of a 3 MWp Solar Farm on 20 kV Distribution System Considering Power Flow and Short Circuit - Nadyanti Larasati; Amien Rahardjo; Hanindito Titah Prameswara; Faiz Husnayain (Faculty of Engineering, Universitas Tanjungpura, 2020)
Currently, renewable energy is under review so that its use can be more widespread in the future. One of the renewable energy sources that are commonly used is solar energy through solar cell technology that can convert solar energy into electrical energy and then becomes one of the components that makes up the solar power plant. The use of the solar power plant can be interconnected with distribution networks in electric power systems, both medium-voltage networks and low voltage networks. In this study, a 3 MWp capacity of solar power plant was conducted with the medium-voltage network system of X City. This interconnection study consisted of power flow and short circuit studies using ETAP 12.6.0 software. The results of the power flow study show the voltage level of each bus has increased by 0.293%-0.926% after interconnection with the solar power plant system, with a value that still matches the SPLN 1:1978 standard of 90% to 105%. Besides, the results of short circuit study show the value of the three-phase short circuit fault current experienced a change in value that is not too significant, with an increase of 1-37 A and a decrease of 1-5 A, with a value that is still according to the protection component rating standard of 25 kA.